Explaining Creative Tourism Development Strategies in Tourism Services (Case study: Isfahan City) - Masoud Taghvaei; Marziye Mousavikifteh; Fatemeh Ghasemi alvari (برنامه ریزی فضایی, 2022)
AbstractCities should take steps to use creative services to develop tourism. In addition to meeting the needs of citizens and tourists, they should also bring satisfaction to them. In this regard, this descriptive-analytical study examined the current state of tourism services in Isfahan City and the role of effective factors in providing appropriate and creative services in the development of the tourism industry. It also seeks to provide creative solutions to reduce problems and make the most of tourism potential, especially tourism services in Isfahan City. The sample size encompasses citizens and tourists (384 people), and experts (40 people) who were selected using the Cochran formula and the snowball sampling method. The data were analyzed using the Fuzzy Promethee technique and EXCEL and GIS software. The results showed that Region 14 is in a very poor condition in terms of creative tourism services due to the lack of effective technologies, responsibility towards the environment, etc. The study suggests taking a positive step in facilitating the creative process of tourism services to improve the status of tourism services.Keywords: Tourism, Creativity, Tourism Services, Fuzzy Promethee.IntroductionTourism is one of the growing industries in the world (Burbano et al., 2022, p. 1). In developing countries where nature and culture tourism is the dominant form of tourism, the development of tourism causes the growth of transportation infrastructure (Kyara et al., 2022, p. 1). Economically sustainable tourism does not destroy the social fabric of the host society (Sørensen & Grindsted, 2021, p. 2). This approach is evident in almost all elements of the national economy that directly or indirectly employs the processes of meeting the needs of tourists (Łapko & Panasiuk, 2019, p. 291). Also, creativity has become a strategy for the development of individual skills, which is used by many cities and destinations in the world and is considered one of the most important success factors of competing cities (Mukhles, 2017, p. 1). Creativity and tourism affect each other and can be synergistic if properly managed (Ardhala et al., 2016, p. 671). In this regard, this study aims to investigate the current state of tourism services in Isfahan City and the role of effective factors in providing appropriate and creative services in the development of the tourism industry. Materials and MethodsThe study is descriptive-analytical in terms of method and applied-developmental in terms of purpose. The data needed for the research were collected from library-documentary and field studies (questionnaires). The studied sample includes citizens, tourists, trustees, and experts. The sample size of citizens and tourists determined by the Cochran formula was equivalent to 383-384 questionnaires. The sample size of experts (40 people) was determined using the snowball sampling method. Also, the Fuzzy Promethee technique and EXCEL and GIS software were used for data analysis. Research FindingsIn this study, 13 indicators in the environmental dimension, 15 indicators in the socio-cultural dimension, 15 indicators in the economic dimension, 14 indicators in the physical dimension, and 13 indicators in the managerial-political dimension have been examined. According to the results of the Fuzzy Promethee technique, Region 14 is in a very poor condition in terms of creative tourism services due to the lack of factors such as new and less effective technologies, a sense of responsibility towards the environment, security issues, the supply of recyclable products and services, favorable natural conditions, and so on. Regions 15, 11, 13, 12, 10, 9, and 7 in Isfahan are in poor to very poor conditions. Therefore, they should be prioritized in planning for fair development and better attraction of tourists. Discussion of Results and ConclusionsCreativity is one of the ways to get rid of existing dead ends and to open new doors for the society. A society that does not have enough creativity lacks life. Considering the results of this study, we can use creativity in different aspects of the society, including creative tourism, providing creative services, etc. Providing creative tourism services could encourage people to travel and visit many places. Also, people would be more willing to spend their time in recreational areas. Tourism services can act as the driver of the economic engine of the society, and by providing these services more favorably, we can attract more people's satisfaction. By creating a pleasant memory of traveling to these places, we can encourage tourists to have more trips. By providing creative solutions in order to improve the status of tourism services, a positive step should be taken in facilitating the creative process of tourism services.References- Akhoundan, R. (2016). Creative tourism, creating a new space in tourism. Tehran: Gilgamesh (in Persian).- Ardhala, A. D., Santoso, E. B., & Sulistyarso, H. (2016). Influence factors on the development of creative industry as tourism destination (Case study: Footwear village in Mojokerto city). Procedia - Social and Behavioral Science, 227, 671- 679.- Babaei, M., & Saeedi, E. (2019). The relationship between the quality of tourism services and the behavioral intentions of sports tourists. Quarterly Journal of Sports Sciences, 11(33), 82-97 (in Persian).- Baste Nagar, M., Hasani, A., & Khakzarbefroui, M. (2017). Conceptual model design of creative tourism. Quarterly Journal of Tourism and Development, 6(2), 81-108 (in Persian).- Burbano, D. V., Valdivieso, J. C., Izurieta, J. C., Meredith, T. C., & Ferri, D. Q. (2022). “Rethink and reset” tourism in the Galapagos Islands: Stakeholders’ views on the sustainability of tourism development. Annals of Tourism Research Empirical Insights, 3(2), 1-12.- Doosti, F., Zaal, M. H., & Ramezanzadeh Lasbouee, M. (2019). Assessing the capacities of creative tourism in Tabriz city. Scientific Quarterly Journal of Urban Tourism, 6(2), 1-13 (in Persian).- Eghbal Moghadam, R., Saeede Zarabadi, Z., & Zabihi, H. (2023). Presenting the creative tourism development model in historical contexts with the approach of start-up businesses in Iran. Journal of Urban Economics and Planning, 4(1), 116-129 (in Persian).- Esmaeilzadeh, H., Haraeeni, M., & Bahrami, M. (2019). Tourists’ satisfaction from quality of tourism services based on SERVQUAL model (Case study: Restaurants in Tehran Darakeh area). Scientific Research Journal of Geography and Planning, 22(66), 1-21 (in Persian).- Fakoor Saghih, A. M., & Hajmandi, N. (2020). Introducing a conceptual model of electronic tourism development in Iran using fuzzy dematel. Scientific-Research Quarterly Journal of Tourism and Development, 10(2), 15-31 (in Persian).- Fletcher, R., Murray Mas, I., Blanco-Romero, A., & Blázquez-Salom, M. (2019). Tourism and degrowth: An emerging agenda for research and praxis. Journal of Sustainable Tourism, 27(12), 1745-1763.- Gheribi, E. (2017). Innovation strategies in restaurant business. Journal of Economics and Organization of Enterprise, 11, 125-135.- Haghkhah, A., & Ebrahimpour, A. (2016). The impact of service quality on tourism industry. 2nd International Conference on Business and Economic Research Proceeding, 1-24.- Heidarzadeh, K., Najafi, K., & Hosseini, A. (2018). The impact of tourism services quality on tourism destination loyalty, considering the mediating role of the tourism destination image and the tourists’ satisfaction. Journal of Tourism Management Studies, 12(40), 115-153 (in Persian).- Hemati, S. (2018). The role of tourism capabilities and infrastructure in the development of modern tourism and economic dynamics with emphasis on the role of systemic variables, especially hotels and accommodations. The Scientific-Research Quarterly Journal of New Attitudes in Human Geography, 10(2), 107-128 (in Persian).- Jamshidi, M. J., Barak Pour, N., & Kalantari, Kh. (2019). Explaining the impact of political economy of religious tourism on the unbalanced distribution of Mashhad tourism services. Journal of Tourism Management Studies, 14(47), 221-260 (in Persian).- Jardim, S., & Mora, C. (2022). Customer reviews sentiment-based analysis and clustering for market-oriented tourism services and products development or positioning. Procedia Computer Science, 196, 199–206.- Jovanovic, S., & Ivana, I. (2016). Infrastucure as important determinant of tourism development in the countries of Southeast Europe. EcoForum Journal, 5(1), 1-34.- Kashfi, M., & Inailo, H. (2017). Investigating urban creativity in the historical settlements of the city for the development of tourism (Case study: Sepah quarter of Qazvin City). The Fourth National Conference on Architecture and Urban Planning, Sustainability and Resilience from Ideal to Reality, pp. 1-15 (in Persian).- Kitsios, F., Champipi, E., & Grigoroudis, E. (2016). Cultural and creative industries innovation strategies for new service development using MCDA. Journal of Operational Research in Business and Economics, 69-83.- Korez-Vide, R. (2012). Promoting sustainability of tourism by creative tourism development: How far is Slovenia?. Innovative Issues and Approaches in Social Sciences, 6(1), 77–102. - Kyara, V. C., Rahman, M. M., & Khanam, R. (2022). Investigating the environmental externalities of tourism development: Evidence from Tanzania. Heliyon, 8(6), 1-13.- Łapko, A., & Panasiuk, A. (2019). Water tourism as a recipient of transport services on the example of Szczecin. Transportation Research Procedia, 39, 290–299.- Lee, J., & Lee, H. (2015). Deriving strategic priority of policies for creative tourism industry in Korea using AHP. Procedia Computer Science, 55, 479-484.- Matteucci, X., Koens, K., Calvi, L., & Moretti, S. (2022). Envisioning the futures of cultural tourism. Futures, 142, 1-9.- Mendes, B., Ferreira, M. C., & Dias, T. G. (2022). Tourism as a service: Enhancing the tourist experience. Transportation Research Procedia, 62, 1–8.- Meshkini, A., Ahmadifard, N., & Movahed, A. (2017). Identification of the zones for creative development in historical context by a tourism approach (Case study: Region 12 of Tehran). Journal of Geographical Urban Planning Research, 5(3), 405-423 (in Persian).- Mihalic, T. (2020). Conceptualising overtourism: A sustainability approach. Annals of Tourism Research, 84, 1-12.- Mukhles, M. (2017). Creative tourism. Journal of Tourism & Hospitality, 6(2), 282.- Nowrozi, S. (2017). Investigating strategies to increase the role of handicrafts in urban tourism (Case study: Isfahan city). MA Thesis, University of Isfahan (in Persian).- Ohridska-Olson, R., & Ivanov, S. (2010). Creative tourism business model and its application in Bulgaria, cultural realms. International University College.- Panahi, A., & Dadashpour Moghadam, M. (2018). Analysis of the role of creative city indicators in urban tourism development (Case study: Isfahan). Quarterly Journal of Research and Sustainable Development of Tourism, 1(3), 1-10 (in Persian).- Pourbagheri, A., Taghvaei, M., & Hairapetian, V. (2021). Development strategies of creative city (Case study: Shiraz). PalArch’s Journal of Archaeology of Egypt/Egyptology, 18(10), 1953-1978.- Prabaharan, B., Arulraj, A., & Rajagopal, V. (2008). Service quality on tourism: application of structural equation modeling. Conference on Tourism in India, pp.143-150.- Rahimi, M., & Pazand, F. (2017). Pattern of the urban creative tourism and present a proposal pattern for Iran (AHP). Quarterly Journal of Innovation and Creativity in Human Sciences, 6(3), 97-124 (in Persian).- Ramezanzadeh Lasboee, M., Zaal, M. H., & Faghihabdollahi, M. (2019). Creative historical cities evaluating in order to cultural tourism development (Case study: Isfahan). Quarterly Journal of Geography and Regional Planning, 9(34), 335-352 (in Persian).- Richard, G. (2011). Creativity and tourism: The state of the art. Annals of Tourism Research, 38(4), 1225–1253.- Richard, G. (2020). Designing creative places: The role of creative tourism. Annals of Tourism Research, (85), 1-11.- Sedaghat, M. (2021). A comprehensive model for sustainable tourism development of Islamic Republic of Iran. Scientific-Research Quarterly Journal of Tourism Planning and Development, 10(36), 288-318 (in Persian).- Shafiei, Z., Farkhian, F., & Mirqader, L. (2014). Isfahan as a creative handicraft city with a tourism development approach. Geographical Society of Iran, 12(43), 251-278 (in Persian).- Shahivandi, A., Taghvaei, M., & Varesi, H. R. (2012). An analysis of status of tourism infrastructures in Isfahan (with emphasis putting on hotels). Journal of Geography and Environmental Planning, 22(4), 91-112 (in Persian).- Sørensen, F., & Grindsted, T. S. (2021). Sustainability approaches and nature tourism development. Annals of Tourism Research, 91, 1-14.- Styvén, M. E., Näppä, A., Mariani, M., & Nataraajan, R. (2022). Employee perceptions of employers’ creativity and innovation: Implications for employer attractiveness and branding in tourism and hospitality. Journal of Business Research, 141, 290–298.- Taleghani, M., & Fatahi, S. (2005). The quality of tourism services and its importance in satisfying tourists. Quarterly Journal of Management, (99-100), 56-63 (in Persian).- Taghvaei, M., Janali Poor, Sh., & Shafiei, M. (2022). Development of creative tourism with emphasis on tourism attractions (Case study: Isfahan City). Journal of Geography and Planning, 26(79), 93-113 (in Persian).- Taghvaei, M., & Kiumarsi, H. (2013). Ecotouristic features analysis and identification of Kaftar Lake using SWOT. Scientific-Research Journal of Geography and Planning, 17(44), 47-71 (in Persian).- Taghvaei, M., & Ranjbar Dastanai, M. (2010). An analysis on the distribution of Northeast tourism facilities and services in Chaharmahal and Bakhtiari province. Journal of Research and Urban Planning, 1(1), 21-48 (in Persian).- Taghvaei, M., Shafaghi, S., & Ghaderi, M. (2017). An analysis of regional imbalances in iran: A case study of north coastal areas. Journal of the Malaysian Institute of Planners, 15(3), 179–192.- Taghvaei, M., & Shafiei, M. (2022). Analysis of indicators and explanation of strategies for achieving urban intelligence: A case study of Isfahan. Scientific Quarterly Journal of Spatial Planning, 12(1-44), 51-80 (in Persian).- Taghvaei, M., Varesi, H. R., & Narimani, M. (2016). An analysis of the effect of urban development plans on realization of sustainable development of metropolis of Isfahan. Journal of Modern Applied Science, 10(3), 1-11.- Taghvaei, M., Varesi, H. R., & Yazdanbakhsh, B. (2014). Site selecting and analyzing the role of motels in tourism development (Case study Isfahan- Shiraz axis). Journal of Research and Urban Planning, 4(15), 17-36 (in Persian).- Tan, S. K., Kung, S. F., & Luh, D. B. (2013). A model of ‘creative experience’ in creative tourism. Annals of Tourism Research, 41, 153–174. - Tomej, K., & Xiang Z. (2020). Affordances for tourism service design. Annals of Tourism Research, 85, 1-9.- Xiao, Y., Tang, X., Wang, J., Huang, H., & Liu, L. (2022). Assessment of coordinated development between tourism development and resource environment carrying capacity: A case study of Yangtze River Economic Belt in China. Journal of Ecological Indicators, 141, 1-13.